Assistive Technology for Communication: ESP32 Microcontroller Based 12-Button Board for Disability Students in SMP Kristen Permata Hati Manado - Chrysantus Padachan; Lianly Rompis; Ryan Singgeta; Julie Rante; Kristian Dame; Alexander Patras; Verna Bokau (Journal of Innovation and Community Engagement, 2024)
Education is the right of every citizen, including students with special needs, such as physical, emotional, mental, intellectual, and social disabilities. To facilitate proper education for students with special needs, a team consisting of permanent lecturers from the Electrical Engineering Study Program at Unika De La Salle Manado cared for and committed to supporting students with special needs at SMP Kristen Permata Hati Manado. The team tried to apply a 12-button board based on an ESP32 microcontroller for students with special needs or students with disabilities at SMP Kristen Permata Hati Manado to make it easier for them to communicate and interact with teachers while in class, especially when examinations are in progress or learning activities is in progress. The input on the 12-button board was processed into sound (speech) which was then sent to the receiver wirelessly so that what was conveyed by students with disabilities in the classroom could be understood by the teacher through the speakers. The results of implementation in school received a good response from the teachers and the students. Teachers were also very helpful in providing students with an understanding of the use of assistive technology.